2022
DOI: 10.3390/ijms23147968
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Application of Starch and Walnut Shells as Biofillers for Natural Rubber (NR) Composites

Abstract: The goal of this study was application of corn starch and ground walnut shells in various amounts by weight as biofillers of natural rubber (NR) biocomposites. Additionally, ionic liquid 1-butyl-3-methylimidazolium chloride (BmiCl) and (3-aminopropyl)-triethoxysilane (APTES) were used to increase the activity of biofillers and to improve the curing characteristics of NR composites. The effect of biofillers used and their modification with aminosilane or ionic liquid on the curing characteristics of NR composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 89 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…The most homogeneous dispersion of the biofiller and curing system was provided by ILs, especially BmiCl (Figure 8d,e). The beneficial effect of ILs on the dispersion of solid components in the elastomer composites was confirmed in our previous work [29,66,75]. On the other hand, Haddad et al [76] confirmed that eggshells were able to interact with imidazolium ILs, which influenced the crystal structure of eggshells.…”
Section: Dispersion Of Ground Eggshells and Curatives In Nr Compositessupporting
confidence: 55%
See 1 more Smart Citation
“…The most homogeneous dispersion of the biofiller and curing system was provided by ILs, especially BmiCl (Figure 8d,e). The beneficial effect of ILs on the dispersion of solid components in the elastomer composites was confirmed in our previous work [29,66,75]. On the other hand, Haddad et al [76] confirmed that eggshells were able to interact with imidazolium ILs, which influenced the crystal structure of eggshells.…”
Section: Dispersion Of Ground Eggshells and Curatives In Nr Compositessupporting
confidence: 55%
“…Silanes, i.e., APTES and TESPTS, increased the onset vulcanization temperature by 15-20 • C compared to 40ES. Moreover, APTES significantly raised the energetic effect of vulcanization compared to rubber compounds with other additives, which proved that it can be used as substance promoting crosslinking reactions [66]. ILs and CTAB did not significantly affect the onset vulcanization temperature and enthalpy of vulcanization compared to 40ES, but it should be noticed that eggshell-filled rubber compounds with these additives exhibited significantly lower onset vulcanization temperature then the unfilled NR.…”
Section: Differential Scanning Calorimetry (Dsc) Analysis Of the Cros...mentioning
confidence: 88%
“…2 However, the silane coupling agents can usually be applied by treating the surface of the filler before the incorporation of the filler into the polymer matrix. 3 In addition, the treatment of filler escalates the fabrication costs of polymer composites since extra work is required, which is limited to some functions and products.…”
Section: Introductionmentioning
confidence: 99%
“…The application of silane coupling agents can improve the polymer matrix‐filler interfacial adhesion, as well as the mechanical properties of polymer composites 2 . However, the silane coupling agents can usually be applied by treating the surface of the filler before the incorporation of the filler into the polymer matrix 3 . In addition, the treatment of filler escalates the fabrication costs of polymer composites since extra work is required, which is limited to some functions and products.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Particle hybridized short fiber reinforced polymer composites have recently attracted the attention of several researchers. [2,[22][23][24][25][26] The second phase was added as particles to the polymer composite to avoid voids and the interfacial gap between the short fiber and polymer matrix. [27] Additionally, particulate reinforcement also works as secondary reinforcement along with short fibers.…”
Section: Introductionmentioning
confidence: 99%